ENDOVASCULAR RENAL DENERVATION EFFICACY AND FEASIBILITY IN END-STAGE KIDNEY DISEASE WITH RESISTANT HYPERTENSION. (June 2018) - Mazza, A.; Dell'Avvocata, F.; Fiorini, F.; Michielan, F.; Compostella, A.F.; Contato, E.; Schiavon, L.; Ramazzina, E.; Casiglia, E.
Abstract : Objective: Sympathetic neural activation is markedly increased in end-stage kidney disease or in dialysis treatment, making hypertension difficult to control. Nephrectomy should be considered to remove the reflex pressor effects of the afferent fibers originating in renal parenchyma, but - due to the high risk of morbidity and mortality associated with the surgical procedure - endovascular renal denervation (RDN) may be an alternative therapeutic strategy to improve blood pressure levels. Figure. No caption available. Design and method: A 47-year-old male, with a long history of hypertension complicated by renal amyloidosis diagnosed in 2009, was admitted to our emergency department 3 times in the last 2 months for hypertensive crises with initial signs of encephalopathy. He followed a dialysis program 3 times a week. At the last admission, his blood pressure was in average 256/142 mmHg under up to 10 antihypertensives medications (nifedipine 120 mg/day, ramipril 20 mg/day, furosemide 500 mg/day, doxazozine 12 mg/day, valsartan 320 mg/day, and hydroclotiazide 25 mg/day). Resistant hypertension was confirmed by the 24-h ambulatory blood pressure measurement (Figure 1). Patient underwent bilateral RDN using a 3rd-generation SpyralTM catheter, a device with multi-electrode configuration that is associated with a reduced procedural time, contrast use and radiation exposure. Results: The procedure was completed without complications. After 48 hours office systolic blood pressure was 40 mmHg lower, and controlled with 4 antihypertensive drugs 1 month later (Figure 2) trough the 24-h ambulatory blood pressure measurement. Conclusions: Bilateral RDN procedure in dialyzed patients with resistant hypertension was feasible without complications and produced an acute and long-term significant decrease in blood pressure. End-stage kidney disease might be the source of a persistently elevated activity of afferent signals to sympathetic nervous system, and the interruption of this loop may favour bllod pressure reduction. This may be obtained by RDN with no need of surgical kidney removal.